Peran Komunikasi Orang Tua Dalam Meningkatkan Perkembangan Kognitif Anak Usia Dini - Listariana Sababalat; Marisa Aulia Gea (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This research discusses the important role of parental communication in improving the cognitive development of early childhood. Effective communication between parents and children is a key element in shaping children's cognitive aspects, which influences the development of children's character, independence and intellectual abilities. Through a qualitative approach with literature study, this research analyzes various related literature and research, highlighting the importance of the role of parents in supporting the guidance and counseling process, becoming partners in child development, communicating with teachers, and involving themselves in school activities. The research conclusion shows that the role of parents in improving cognitive abilities in early childhood has a significant impact and cannot be ignored. Therefore, it is important for parents to understand and implement their parental role actively and collaboratively to ensure children's welfare and optimal development, both inside and outside the home environment.